Binder Engineering of Leather Shaving Waste–Based Collagen Composite for Shoe Insole Application: Mechanical–Moisture Trade-Off Analysis - Winata, Wahyu Fajar; Nurbalia, Elis; Rahmayani, Elyka; Dewi, Zahra Saadiya; Tiyastuti, Rini (Chemistry Department, Universitas Islam Indonesia, 2026)
Leather shaving waste (LSW) generated from the tannery industry contains chromium-stabilized collagen fibers that are environmentally persistent and difficult to manage. This study investigates the valorization of LSW into leather board for shoe insole applications through binder system engineering. LSW was neutralized using alkaline treatment and compounded with polyester resin and polyvinyl acetate (PVAc), followed by press molding. Mechanical properties and water absorption were evaluated according to SNI 1294-2009 standards. The results show that binder composition significantly influences interfacial adhesion, mechanical strength, and moisture sensitivity. Formulation F3 exhibited superior tensile and tear strength due to enhanced fiber–matrix bonding, while formulation F4 demonstrated improved water resistance. An Engineering Performance Index (EPI) was introduced to integrate mechanical strength and moisture stability, revealing a clear trade-off between maximum mechanical performance and durability against water absorption. Formulation F6 presented a more balanced mechanical–moisture profile suitable for practical insole applications. These findings confirm that binder engineering governs the structure–property relationship of collagen-based composites and provides a sustainable pathway for circular utilization of tannery solid waste.